Tertiary Lymphoid Structure in Dental Pulp: The Role in Combating Bacterial Infections - Ruiqi Li; Fan Gu; Linlin Peng; Tingting Huan; Zhuo Zhou; Yaling Song; Jinmei He; Kaili Ye; Yao Sun; Tiejun Li; Miao He; Zhuan Bian; et al. (Advanced Science)
Abstract Tertiary lymphoid structure (TLS) is associated with various pathologies, including those of cancers and chronic infections. Depending on the organ, multiple factors regulate the formation of TLS. However, the role of TLS in immune response and the molecules that drive its formation remain uncertain. The dental pulp, includes a few immune cells surrounded by rigid mineralized tissue, and opens to the outside through the apical foramen. Owing to this special organization, the dental pulp generates a directional immune response to bacterial infection. Considering this aspect, the dental pulp is an ideal model for comprehensively studying the TLS. In the present study, single‐cell RNA sequencing of healthy and inflamed human dental pulp reveals known markers of TLS, including C‐C motif chemokine ligand 19 (CCL19), lysosome‐associated membrane glycoprotein 3 (LAMP3), CC chemokine receptor 7 (CCR7), and CD86, present in inflamed dental pulp. Compared with the healthy pulp, types and proportions of immune cells increase, along with enhanced cellular communication. Multiple immunofluorescence staining reveals that typical TLS emerges in dental pulp with pulpitis, consistent with the high expression of CC chemokine ligand 3 (CCL3), which may be a key driver of TLS formation. Moreover, TLS is also observed in a mouse model of pulpitis. These findings collectively offer insights into the formation and function of TLS in response to infection.